Analysis of Histones and Chromatin in Xenopus laevis Egg and Oocyte Extracts - Banaszynski, Laura A. (2010)
Histones are the major protein components of chromatin, the physiological form of the genome in all eukaryotic cells. Chromatin is the substrate of information-directed biological processes, such as gene regulation and transcription, replication, and mitosis. A long-standing experimental model system to study many of these processes is the extract made from the eggs of the anuran Xenopus laevis. Since work in recent years has solidified the importance of post-translational modification of histones in directing biological processes, the study of histones in a biochemically dissectible model such as Xenopus is crucial for the understanding of their biological significance. Here we present a rationale and methods for isolating and studying histones and chromatin in different Xenopus egg and oocyte extracts. In particular, we present protocols for the preparation of: cell-free egg and oocyte extract; nucleoplasmic extract (“NPE”); biochemical purification of maternally-deposited, stored histones in the oocyte and the egg; assembly of pronuclei in egg extract and the isolation of pronuclear chromatin and histones; and an extract chromatin assembly assay. We also demonstrate aspects of the variability of the system to be mindful of when working with extract and the importance of proper laboratory temperature in preparing quality extracts. We expect that these methods will be of use in promoting further understanding of embryonic chromatin in a unique experimental system.